2016
DOI: 10.1590/s1808-185120161501147147
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Spine Fractures in Motorcycle Accident Victims

Abstract: Objective: To analyze the incidence of spinal injuries between 2000-2010 due to motorcycle accidents and the relation to the increase in motorcycle sales in the same period, as well as the anatomical distribution of these spinal injuries. Methods: Data were collected from 1,295 records of patients who have suffered spinal injury resulting from motorcycle accidents admitted to the ward TRM (Spinal Cord Trauma) of the Hospital Geral do Estado da Bahia from 2000 to 2010 in this retrospective study. We selected 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…The most affected medullar segments are the cervical and thoracic regions, caused by firearm accidents, followed by accidents caused by falls and diving in shallow water 10,12,13 , corroborating the findings of this research. The total medullary trauma of the cervical segment and the initial part of the thoracic spine may result in quadriplegia and, in other situations, the partial dissection of other parts of the spine will result in paraplegia as a sequel, according to this investigation and the analyzed study 14 .…”
Section: Discussionsupporting
confidence: 89%
“…The most affected medullar segments are the cervical and thoracic regions, caused by firearm accidents, followed by accidents caused by falls and diving in shallow water 10,12,13 , corroborating the findings of this research. The total medullary trauma of the cervical segment and the initial part of the thoracic spine may result in quadriplegia and, in other situations, the partial dissection of other parts of the spine will result in paraplegia as a sequel, according to this investigation and the analyzed study 14 .…”
Section: Discussionsupporting
confidence: 89%
“…Several articles concerning the epidemiological features of spinal fractures have been published. [35] Hu et al [6] reported that the incidence rate of traumatic spinal fractures was 64 per 100,000 in Manitoba province, Canada. Cooper et al [7] estimated the incidence rate in Rochester, Minnesota which was 117 per 100,000.…”
Section: Introductionmentioning
confidence: 99%
“…Os seguimentos medulares mais acometidos são as regiões cervical e torácica, causados por acidentes por arma de fogo, seguidos dos acidentes oriundos de quedas e mergulho em águas rasas 10,12,13 , estando de acordo com os achados nesta pesquisa. O trauma medular total do seguimento cervical e a parte inicial da coluna torácica pode trazer como consequência a tetraplegia e, em outras situações, a dissecção parcial de outras partes da coluna trará como sequela a paraplegia conforme estudo verificado 14 e averiguado nesta investigação.…”
Section: Discussionunclassified